IMPROVEMENT OF THE CHILD CARE FIRST YEAR OF LIFE IN SURGICAL DISEASES - V. G. Trepel; M. A. Shishov (Медицинский вестник Юга России, 2014)
Purpose: To compare the performance and structure of infant mortality in Russia and Rostov region, as well as the establishment of the general principles of the system of internal controls designed to improve the organization of medical care for children of the first year of life in surgical diseases.Materials and methods: The infant mortality rate specified in the official documents of the executive authorities was monitored, as well as the analysis of legal acts.Results: The performance of the Rostov region for the last 8 years above the national average, while the «wavy» character «infant mortality curve» refers to the need to improve organizational measures aimed at reducing child mortality, and therefore the actual allocated for medical organization obligatory components of internal control.Summary: The decline in infant mortality can be achieved by constructing a system of internal control at the level of the medical organization comprising such components as the control of health care provided for children of the first year of life in surgical diseases caused by defects and developmental abnormalities.